2014
DOI: 10.7150/ijms.9623
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Spasm: Review and Update

Abstract: Coronary artery spasm (CAS), an intense vasoconstriction of coronary arteries that causes total or subtotal vessel occlusion, plays an important role in myocardial ischemic syndromes including stable and unstable angina, acute myocardial infarction, and sudden cardiac death. Coronary angiography and provocative testing usually is required to establish a definitive diagnosis. While the mechanisms underlying the development of CAS are still poorly understood, CAS appears to be a multifactorial disease but is not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
145
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(174 citation statements)
references
References 143 publications
0
145
0
11
Order By: Relevance
“…The inflammation may cause endothelial dysfunction. It leads to a reduction in the release of nitric oxide and the induction of ischemia (16). A previous study reported that endothelial dysfunction in patients with vasculitis improved after the suppression of inflammation (17).…”
Section: Discussionmentioning
confidence: 99%
“…The inflammation may cause endothelial dysfunction. It leads to a reduction in the release of nitric oxide and the induction of ischemia (16). A previous study reported that endothelial dysfunction in patients with vasculitis improved after the suppression of inflammation (17).…”
Section: Discussionmentioning
confidence: 99%
“…7) Intracoronary administration of vasopressin has been shown to constrict small coronary arteries, causing subendocardial ischemia 9) and Ca 2+ channel blocker is known to possess a potent coronary vasodilator effect, which has been widely used for patients with vasospastic angina. 1) Tetramethylpyrazine significantly inhibited the vasopressin-induced subendocardial ischemia, which was not observed by the vehicle, indicating that tetramethylpyrazine may possess an anti-ischemic effect. Similar results were reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…While β-blockers, Ca 2+ antagonists and/or nitrates have been used for the treatment of patients with angina pectoris according to therapeutic guidances of western medicine, 1) tetramethylpyrazine (TMP), an extract of the herb Ligusticum wallichii FRANCH. (chuanxiong), has been widely applied for the treatment of ischemic heart disease as a complementary and/or alternative medicine in China.…”
mentioning
confidence: 99%
“…In the late 1990s and early 2000s, genetic mutations were found to be associated with CAS. Nonetheless, coronary vascular smooth muscle cell hyper-reactivity seems to constitute the substrate for CAS" [6,7]. Oros P et al, writed that "Sudden death is an important but widely under-recognized consequence of stroke.…”
Section: From Literaturementioning
confidence: 99%